Can pantheism explain the existence of the universe? - Oberle, Thomas (Religious studies, 2026)
Many traditional theists maintain that God is the ultimate explanation of the universe, for why anything exists at all. For the traditional theist, only a being who is fundamental and transcendent can provide an ultimate ground and explanation of the universe. This requirement that God transcend the universe in order to ultimately explain it poses a challenge for pantheism, the view that God is numerically identical with the universe. If God is identical with the universe, and God is supposed to be the ultimate explanation of the universe, the result is an instance of circular explanation. And circular explanations are allegedly illegitimate. In this article, I develop two explanatory models in an attempt to show that pantheism is consistent with non-circular explanations of the universe. All else being equal, I argue that pantheism is not explanatorily deficient in comparison to traditional theism.